Public Enforcement and Initial Public Offering Reporting Quality in Weak Institutional Environments: Evidence from a Random Experiment in China - Manyi Fan; Kai Guo; Bin Ke (Management Science, 2026)
Using China’s randomized pre-initial public offering on-site inspection program, we examine the causal effects of proactive public enforcement on the financial reporting quality of initial public offering applicants. Our analysis shows that the program enhances the reporting quality of selected applicants by screening out firms with questionable financial disclosures. More importantly, it generates a significant deterrence effect, discouraging future applicants from submitting low-quality financial reports. However, we also find that public enforcement can lead to the rejection of some firms that may otherwise merit approval. These findings highlight both the benefits and costs of employing public enforcement to improve financial reporting in settings with weak institutional oversight. This paper was accepted by Eric So, accounting. Funding: K. Guo acknowledges financial support from the National Natural Science Foundation of China [Grants 72302146 and 72132006], the Shanghai Pujiang Program, and the National Social Science Fund of China [Grant 22AZD034]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.05042 .